206 MHz fully stabilized all-PM dispersion-managed figure-9 fiber laser comb - Shotaro Kitajima; Kwangyn Jung; Norihiko Nishizawa (Scientific Reports, 2024)
Abstract High-repetition-rate optical frequency combs are useful for precision spectroscopy because of their high power per comb mode, but conventional high-repetition-rate lasers do not have a broad enough spectrum. In this study, a fully stabilized polarization-maintaining figure-9 mode-locked fiber laser with a high repetition rate of 206 MHz and a broad spectrum was demonstrated by employing simultaneous control of cavity dispersion and length. The laser exhibited a 3 dB spectral bandwidth of 88 nm and a compressed pulse width of 66 fs. Additionally, f CEO and f rep phase locking were implemented, resulting in low (0.21 rad) in-loop carrier-envelope-offset frequency phase noise. To the best of our knowledge, this is the widest spectrum bandwidth and shortest pulse duration directly obtained from an all-PM figure-9 fiber laser oscillator to date. The combination of high repetition rate and broad spectral range makes this system very useful for a wide range of applications, especially in the field of precision spectroscopy.